Answer:
The next three terms are (-3n - 2), (-3n - 5), (-3n - 8)
Explanation:
∵ T(n) = 1 - 3n, where
- n is the position of the term in the sequence
To find the next three terms substitute n by n + 1, n + 2, n + 3
∵ n = n + 1
∴ T(n + 1) = 1 - 3(n + 1)
∴ T(n + 1) = 1 - 3(n) - 3(1)
∴ T(n + 1) = 1 - 3n - 3
∴ T(n + 1) = -3n - 2
∴ T(n + 1) = -3n -2
∵ n = n + 2
∴ T(n + 2) = 1 - 3(n + 2)
∴ T(n + 2) = 1 - 3(n) - 3(2)
∴ T(n + 2) = 1 - 3n - 6
∴ T(n + 2) = -3n - 5
∴ T(n + 2) = -3n -5
∵ n = n + 3
∴ T(n + 3) = 1 - 3(n + 3)
∴ T(n + 3) = 1 - 3(n) - 3(3)
∴ T(n + 3) = 1 - 3n - 9
∴ T(n + 3) = -3n - 8
∴ T(n + 3) = -3n - 8
∴ The next three terms are (-3n - 2), (-3n - 5), (-3n - 8)